TYPES AND DISTRIBUTION OF CORAL REEF ON THE KARIMATA COAST, WEST KALIMANTAN - Noor C.D. Aryanto; Yani Permanawati (Marine Geological Institute of Indonesia, 2009)
The identification of quality and condition of the coral reef in the study areas will support the biological diversity and it frequently contains a valuable assortment of natural resources, conservation of marine biota. The environmental problem particularly on the coastal area needs a more comprehensive management due to the complexity of the rapidly growth. Karimata Archipelago geographically is located between 108o40' - 109o10' E and 1o25' - 1o50' S and administratively belongs to the Ketapang Regency (approximate 100 km west side of Ketapang). In the study area, the growth of coral reef is dominated by non-Acropora type arised between the depths 3-15m. The condition is somewhat good to good. Karimata Archipelago consist of two big islands they are Karimata Island (Studied area) and Serutu Island and also some other isles, with the topography from low land to high land having the height of about 1030 meters from sea level. Keywords: Coral reef, Karimata coast, West Kalimantan. Identifikasi kualitas dan kondisi terumbu karang di daerah penelitian dapat menopang keanekaragaman biologi yang pada akhirnya dapat berperan sebagai kawasan konservasi biota laut. Masalah kepekaan lingkungan khususnya di wilayah pantai dan pesisir memerlukan penanganan yang lebih komperhensif, karena kawasan ini relatif lebih kompleks selain perkembangannya yang demikian pesat. Gugusan kepulauan Karimata secara geografi menempati posisi 108o40' - 109o10' BT and 1o25' - 1o50' LS dan secara administrasi masuk dalam Kabupaten Ketapang (lebih-kurang berjarak 100 km ke arah barat dari Ketapang). Di lokasi telitian, keberadaan terumbu karangnya didominasi oleh jenis non-Acropora yang tumbuh baik pada kedalaman antara 3 hingga 15 m. Terumbu karang yang dijumpai dengan kondisi agak baik hingga baik. Kepulauan Karimata terdiri dari 2 pulau besar, P. Karimata di mana lokasi studi terletak dan P.Serutu dan beberapa pulau-pulau kecil dengan topografi dari dataran rendah hingga dataran tinggi (1030 m) di atas permukaan laut. Kata kunci:Terumbu karang, Pantai Karimata, Kalimantan Barat.